2008
DOI: 10.1667/rr0848.1
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer in French and Czech Uranium Miners: Radon-Associated Risk at Low Exposure Rates and Modifying Effects of Time since Exposure and Age at Exposure

Abstract: Radon is recognized as a public health concern for indoor exposure. Precise quantification derived from occupational exposure in miners is still needed for estimating the risk and the factors that modify the dependence on cumulated exposure. The present paper reports on relationship between radon exposure and lung cancer risk in French and Czech cohorts of uranium miners (n = 10,100). Miners from these two cohorts are characterized by low levels of exposure (average cumulated exposure of less than 60 WLM) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
117
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 18 publications
7
117
1
2
Order By: Relevance
“…Local hyperplasia due to chronic exposure to radon progeny that occurs only beyond a threshold dose rate can provide an explanation for the inverse dose-rate effect and its disappearance at low cumulative doses as observed in several epidemiological studies of lung cancer among uranium miners (Lubin et al 1995;Tomasek et al 2008;Walsh et al 2010). Tomasek et al (2008) reported a threshold of 4 WL, which is in good agreement with the threshold based on the present simulations.…”
Section: Area Ratio (%)supporting
confidence: 91%
“…Local hyperplasia due to chronic exposure to radon progeny that occurs only beyond a threshold dose rate can provide an explanation for the inverse dose-rate effect and its disappearance at low cumulative doses as observed in several epidemiological studies of lung cancer among uranium miners (Lubin et al 1995;Tomasek et al 2008;Walsh et al 2010). Tomasek et al (2008) reported a threshold of 4 WL, which is in good agreement with the threshold based on the present simulations.…”
Section: Area Ratio (%)supporting
confidence: 91%
“…There are three cohorts of uranium miners, the Czech (n = 10,000), the French (n = 5,000) and German (n = 60,000) cohorts. The cohorts are characterised by a large size, early start dates (between the 1940s and 1950s), a long follow-up period (more than 30 years on average), a small percentage of participants lost to follow-up, and a large number of cancer and non-cancer deaths (Tomasek et al, 2008;Vacquier et al, 2008;Kreuzer et al, 2010). Individual information on radiation exposure (radon progeny, long-lived radionuclides, and external gamma radiation) is available for all cohort members and organ doses have already been calculated for several target organs.…”
Section: Epidemiological Issuesmentioning
confidence: 99%
“…In Europe, a tight collaboration between Czech, French, and German investigators already exists, based on several former common EC projects on uranium miners (Tirmarche et al, 2003;Tomasek et al, 2008;Tirmarche et al, 2010). Presently, the pooling of data from the three European and three Canadian miner studies is in preparation.…”
Section: Collaboration Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…были опубликованы результаты нескольких объ-единенных эпидемиологических исследова-ний связи облучения людей радоном в жи-лищах с раком легкого методом «случай-контроль», начатых еще в конце 1980-х гг. [10,[19][20][21][22], а также нескольких объединен-ных эпидемиологических исследований среди шахтеров с относительно низкими уровнями суммарной экспозиции [15,16,23,25]. Эти результаты были тщательно про-анализированы специально созданной в 2005 г. Рабочей группой МКРЗ, и в ноябре 2009 г. Комиссия одобрила «Заявление по радону», а в 2010 г. была выпущена Пуб-ликация 115 [7,12], в которой подтвер-ждается, что дополнительный абсолют-ный риск возникновения рака легкого, обусловленный радоном и его ДПР, рас-считанный для облучения в жилищах, со-поставим с оценками, полученными для шахтеров при низких уровнях экспози-ции.…”
unclassified